Post-colonial representation of women's education in African novels - Grace Niwabiine; Johnson Ocan (Journal of Social, Humanity, and Education, 2025)
Purpose: This study investigates the representation of women’s education in Africa within the postcolonial context. The research aims to assess the portrayal of women’s education as a tool for empowerment and social change, focusing on the socio-political implications of post-colonialism and its impact on women’s educational experiences, considering the ongoing legacies of colonialism. Research methodology: In terms of Methodology, a comparative literary analysis was employed, to analyze thematic and narrative elements of women's education. A purposive sampling method was used to select five significant African novels. Data was further scrutinized through secondary literature that relates to themes of post-colonialism and women's education in African contexts. This analysis will deploy close reading and qualitative literary analysis and most of the data obtained were analyzed thematically. Results: The findings reveal that themes such as the tension between modern education and traditional expectations were recurrent in the five novels. Conclusions: , this study affirms that African post-colonial novels do not only serve as literary expressions but are critical sites for investigating gender roles, education and colonial legacies reinforcing the idea that education as portrayed in the selected novels is a key avenue for women empowerment and societal transformation Limitations: The research was limited by focusing on few authors, which may not fully capture the experiences of other authors in another culture or locality. Contribution: This article illustrates how education empowers women, to challenge oppressive systems and redefine their identities and offers insights into the impact of women’s education, focusing on its portrayal in post-colonial novels.